Analisis Pengaruh Struktur Dewan Direksi terhadap Kinerja Perusahaan - Meiliana, Meiliana; Julia, Iven (Global Financial Accounting Journal, 2022)
Purpose - This study aims to determine the effect of the board structure on company performance. This study has 6 independent variables, which consist of the size of the board of directors, independent directors, board of directors meetings, board of directors education, female directors, and managerial ownership. Research Method - The sample used in this research is quantitative data with a purposive sampling technique. Based on the criteria, the samples collected from 473 companies in the period 2014-2018. The sample data is tested using panel data regression. Findings - This study concludes that all the independent variables have no significant effect on company performance. Board of directors still needs to be controlled to achieve good performance. Independent directors rarely interfere on other director decision. Board of director’s meetings only incurs unnecessary expenses. Board of director's education is just a qualification. Women's board of directors in each country could have difference effect because of cultural differences. There are still many directors in public companies that do not have ownership in the company, so there is still no visible effect on managerial ownership. Implication - The findings of this study imply that corporate governance still needs to be strengthened to improve company performance. There are still many problems within the company due to poor governance.